Emerging trends: Apps in event management - Aggarwal V.; Ansari N. (My University, 2025)
This paper will present an experiment in which an event management app named 'Technex' was made for android, which hosted several features to assist the crowd participating in the event. The paper analyses the public reception of the app and how it assisted the people. Further, this paper presents the concept of how this app can be extended from an institute level to city level and helps the people in different aspects using open data. Copyright 2014 ACM.